A CONTRIBUTION TO THE PHYSIOLOGICAL DIFFERENTIATION OF PNEUMOCOCCUS AND STREPTOCOCCUS, AND TO METHODS OF STAINING CAPSULES - Hiss, Philip Hanson (The Rockefeller University Press, 1905)
By morphological examination and with current cultural methods a clear differentiation cannot always be made between pneumococci and streptococci. The chief differential character usually depended upon is the capsule of the pneumococcus. Well-marked capsules, however, may occur on organisms which have with reason been classified as streptococci. On the other hand, capsules may not he demonstrable on pneumococci by the usual methods, especially when growing on artificial culture media. The usual cultural characters and reactions are at best not diagnostic, and are subject to variations which may render them useless as evidence of specific difference. The experiments recorded in this paper, however, afford some evidence that there are well-marked differences between the metabolic activities of pneumococci and streptococci, which may prove useful in the differentiation of these organisms. These differences in metabolism become apparent when the pneumococci and streptococci are cultivated in an alkaline serum medium, or in a serum medium to which the carbohydrate, inulin, has been added. Pneumococci slowly produce acid in the alkaline serum.